The Effect of Counselling about Exclusive Breastfeeding on the Knowledge and Attitude of Pregnant Mother - Hassita Nadia Silkviana; Sholihul Absor; Annisa Nurida; Gina Noor Djalilah (Universitas Muhammadiyah Yogyakarta, 2021)
Preliminary : Giving a exclusive breast milk for 0-6 month baby are very important to provide a better life for baby growth. The exclusive breast milk at Indonesia has reached the target that was 65.16 percent. In east Java it has reached until 79.20 percent suitable with the advice from ministry of health, that was 80 percent. The percentage of exclusive breast milk at Sraturejo village was so low that was 42.96 percent. Then this problem needs to be studied further more. This research use counselling methods provide information, in still confidence in the community abd increase knowledge, skills and attitudes. Purpose : This research have a purpose to know the effect of exclusive breast milk’s counseling for the knowledge and attitude of expectant mother in Desa Sraturejo, the region of Puskesmas Kecamatan Baureno Kabupaten Bojonegoro at 2019. Method : This research have cross sectional with one group pretest – post test as the types of research. The participants from this research was all of the expectant mother in Sraturejo village , the region of Public Health Center Baureno Distric, Bojonegoro Regency at October 2019 with 32 person as the participants for this research. The sample for this research was a expectant mother who attend to exclusive breast milk’s counseling in Sraturejo Village the region of Public Health Center Baureno Distric and Sraturejo Village Baureno District, Bojonegoro Regency. The instrument used in the research was a questionnaire with data analytics use paired sample t-test statistic. Result : From the research result show that knowledge before the counseling program got score 25.66 and attitude got score 9.50. After having a counseling as the score have improve to 29.63 as the knowledge’s score and 14.00 as the attitude’s score. Conclusion : From the research result can be concluded that a counseling as the way of promoting healthiness influence people to improve the knowledge and attitude from expectant mother to giving exclusive breast milk. Most of the expectant mother was a working mother and 2 of them have a elementary school’s level of education.